Automated Solid‐Phase Synthesis of a β‐(1, 3)‐Glucan Dodecasaccharide. Issue 37 (16th August 2013) - Weishaupt, Markus W.; Matthies, Stefan; Seeberger, Peter H.
Abstract β‐Glucans are a group of structurally heterogeneous polysaccharides found in bacteria, fungi, algae and plants. β‐(1, 3)‐D‐Glucans have been studied in most detail due to their impact on the immune system of vertebrates. The studies into the immunomodulatory properties of these glucans are typically carried out with isolates that contain a heterogeneous mixture of polysaccharides of different chain lengths and varying degrees of branching. In order to determine the structure–activity relationship of β‐(1, 3)‐glucans, access to homogeneous, structurally‐defined samples of these oligosaccharides that are only available through chemical synthesis is required. The syntheses of β‐glucans reported to date rely on the classical solution‐phase approach. We describe the first automated solid‐phase synthesis of a β‐glucan oligosaccharide that was made possible by innovating and optimizing the linker and glycosylating agent combination. A β‐(1, 3)‐glucan dodecasaccharide was assembled in 56 h in a stereoselective fashion with an average yield of 88 % per step. This automated approach provides means for the fast and efficient assembly of linker‐functionalized mono‐ to dodecasaccharide β‐(1, 3)‐glucans required for biological studies.